2019
DOI: 10.3892/ol.2019.11032
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA reverses EGF‑ and TGF‑β1‑mediated epithelial‑mesenchymal transition in HepG2 cells via the PI3K/Akt/ERK signaling pathway

Abstract: Epithelial-to-mesenchymal transition (EMT) is an essential phenotypic conversion involved in cancer progression. Epidermal growth factor (EGF) and transforming growth factor (TGF)-β1 are potent inducers of the EMT. Tanshinone IIA (Tan IIA) is a phenanthrenequinone extracted from the root of Salvia miltiorrhiza Bunge, and its anticancer activity has been demonstrated in numerous studies. However, the mechanisms of action underlying Tan IIA in EGF-and TGF-β1-induced EMT in HepG2 cells remain unknown. Multiple as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“… 2013 ), and the PI3K/Akt/ERK signalling pathway (Zhang et al. 2019 ). In the present study, the administration of TGF-β1 dramatically promoted the cell viability and EMT, curcumin treatment reversed these affects via the TLR4/NF-κB and the PI3K/AKT pathways, illustrating the mechanism behind curcumin’s anti-EMT activity.…”
Section: Discussionmentioning
confidence: 99%
“… 2013 ), and the PI3K/Akt/ERK signalling pathway (Zhang et al. 2019 ). In the present study, the administration of TGF-β1 dramatically promoted the cell viability and EMT, curcumin treatment reversed these affects via the TLR4/NF-κB and the PI3K/AKT pathways, illustrating the mechanism behind curcumin’s anti-EMT activity.…”
Section: Discussionmentioning
confidence: 99%
“…Tanshinone IIA (Tan IIA) is the main phytochemical isolated from S. miltiorrhiza and is the main contributor to its beneficial cardiovascular effect. Besides, several studies have revealed other medicinal effects of Tan IIA, including anti-tumor, antiproliferation, and anti-inflammatory effects in various cancers, such as non-small-cell lung cancer, liver cancer, cervical cancer, colorectal cancer, and gastric cancer (Sui et al, 2017;Zhang et al, 2018;Liu et al, 2019;Wang R. et al, 2019;Zhang et al, 2019). Additionally, there are also reports that Tan IIA can be used to treat arthritis (Jia et al, 2017;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tanshinone IIA (Tan IIA) inhibits EGF and TGF-β1-induced EMT in HepG2 cells by inactivating the PI3K/AKT/ERK pathway. 17 In addition, studies have found that non-SMC condensin I complex subunit G (NCAPG) acts as an oncogene in liver cancer and promotes cell proliferation and reduces apoptosis by activating the PI3K/AKT/FOXO4 pathway. 18 Nevertheless, whether Rop could affect the activation of PI3K/AKT in GC by regulating miR-520a-3p remains unclear.…”
Section: Introductionmentioning
confidence: 99%